Children's Active Play during the COVID-19 Pandemic in Jakarta - Irene Virta Olivianti; Agustina Hendriati (Journal of Educational, Health and Community Psychology, 2022)
The aim of this research is to describe active play among children in Jakarta during the COVID-19 pandemic. Active play is necessary for optimal child development, yet there are a lot of restriction to do so amidst the pandemic. Therefore, it is important to understand how children allowed active play while being restricted spatially. Main data were collected using semi structured online interview, analysed using qualitative descriptive approach. Four mothers of children from three toÂ four years old participated, chosen purposively as typical samples. All of the four children involve in active play and show that the domain of locomotor, object, social and pretend play are present. The intensity of children to play outdoor seems less than usual. Since most of the activities are home-based, children often feel annoyed, outraged, and cry easier than they usually do. However, the problem can be solved if supportive environment is available that is parents are involved in active play every day during the pandemic.